2023
DOI: 10.1037/pne0000318
|View full text |Cite
|
Sign up to set email alerts
|

Detecting symptom exaggeration in compensation-seeking individuals, psychotherapy clients, and individuals referred for job assessments: Psychometric features of the French and Dutch versions of the Self-Report Symptom Inventory.

Abstract: Objective: The Self-Report Symptom Inventory (SRSI) is a relatively new instrument to detect symptom exaggeration. It contains a mix of plausible and pseudosymptoms, the rationale being that people who intend to exaggerate symptoms will overendorse both types of symptoms, whereas individuals responding truthfully will selectively endorse primarily plausible symptoms. The present study examined whether there are any differences in Dutch and French versions of the SRSI as a first step in determining their psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In stark contrast to this outdated practice, experts now seem to agree that patient groups cannot be unequivocally considered "bona fide comparison groups" for experimental simulation studies because invalid test results can and do occur outside of the medicolegal/forensic context. For example, in one of the studies included in this special issue, the percentage of SVT failure was as high as 18.1% in a group of individuals assessed prior to psychotherapeutic treatment (Dandachi-FitzGerald et al, 2023), and previous studies have observed similar failure rates in other clinical samples with different SVTs (Bodenburg et al, 2022;Dandachi-FitzGerald et al, 2016;Schroeder & Martin, 2022). Of note, certain SVTs sometimes seem to yield a relatively high number of positive results even in nonclinical contexts Zahid et al, 2023).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In stark contrast to this outdated practice, experts now seem to agree that patient groups cannot be unequivocally considered "bona fide comparison groups" for experimental simulation studies because invalid test results can and do occur outside of the medicolegal/forensic context. For example, in one of the studies included in this special issue, the percentage of SVT failure was as high as 18.1% in a group of individuals assessed prior to psychotherapeutic treatment (Dandachi-FitzGerald et al, 2023), and previous studies have observed similar failure rates in other clinical samples with different SVTs (Bodenburg et al, 2022;Dandachi-FitzGerald et al, 2016;Schroeder & Martin, 2022). Of note, certain SVTs sometimes seem to yield a relatively high number of positive results even in nonclinical contexts Zahid et al, 2023).…”
mentioning
confidence: 95%
“…Also noteworthy, there were no order effects. Along similar lines, Dandachi-FitzGerald et al (2023) administered the Self-Report Symptom Inventory (SRSI; Merten et al, 2016; for a review, see Merten et al, 2022) in either Dutch or French to a relatively large sample consisting of compensation-seeking individuals, psychotherapy clients, and job applicants. Consistent with the hypothesis that the Dutch and French versions of the SRSI are equivalent, the mean scores and failure rates were strikingly similar in both languages.…”
mentioning
confidence: 99%